2007
DOI: 10.1002/qua.21339
|View full text |Cite
|
Sign up to set email alerts
|

Swift hopping gallium over [AlO4] tetrahedra in Ga/ZSM‐5: A DFT study

Abstract: ABSTRACTϪ zeolite fragment at T12 position were found. These isomers are turning into each over with low activation energy barrier and gallium fragment revolves around [AlO 4 ] Ϫ tetrahedron by hopping between cationic positions. Activation energies of gallium fragment hopping were computed and compared for different gallium containing cations. Those barriers were found to be times less than the activation energies of catalytic processes on gallium-exchanged zeolite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…High-silica zeolites modified with gallium are known as effective catalysts for aromatization of light alkanes. , It is generally believed that these catalysts have a bifunctional nature: the role of the modifying Ga cations in these processes is usually associated with the dehydrogenation function, whereas the residual Brønsted acid sites in the zeolite are thought to promote secondary reactions such as oligomerization, cracking, and ring-closure steps. Despite numerous experimental and computational studies , reporting on the chemistry and reactivity of the intrazeolite gallium species, there is still considerable debate on the structure of the active site and the relevance of Lewis or Brønsted acid sites in the various constituent reactions of alkane aromatization …”
Section: Introductionmentioning
confidence: 99%
“…High-silica zeolites modified with gallium are known as effective catalysts for aromatization of light alkanes. , It is generally believed that these catalysts have a bifunctional nature: the role of the modifying Ga cations in these processes is usually associated with the dehydrogenation function, whereas the residual Brønsted acid sites in the zeolite are thought to promote secondary reactions such as oligomerization, cracking, and ring-closure steps. Despite numerous experimental and computational studies , reporting on the chemistry and reactivity of the intrazeolite gallium species, there is still considerable debate on the structure of the active site and the relevance of Lewis or Brønsted acid sites in the various constituent reactions of alkane aromatization …”
Section: Introductionmentioning
confidence: 99%
“…Ga-containing zeolites are known as efficient catalyst for light alkane dehydrogenation and aromatization . Recent experimental and theoretical studies , have contributed significantly to our understanding of the mechanisms underlying alkane activation over these catalysts. It has been concluded that a rather low but stable catalytic activity of reduced Ga/ZSM-5 zeolites associates with the presence of extra-framework Ga + cations in the microporous matrix. , The initial C−H bond activation proceeds over the Lewis acid−base pair formed by Ga + ion and an adjacent basic framework oxygen of the zeolite ( I + RH → II , Scheme )…”
mentioning
confidence: 99%